In-situ monitoring system for yak meat freshness based on flexible multi-modal sensing and deep feature fusion - Wenhao He; Nuo Li; Jianghan He; Fumin Chi; Xiaoshuan Zhang (Food Control, 2026)

W1/O/W2 emulsion stabilized by β-lactoglobulin/exopolysaccharides/epigallocatechin gallate complex: Protective effects on Lactobacillus plantarum A81 during storage, pasteurization and gastrointestinal digestion - Cuicui Duan; Yi Zhang; Hongru Wang; Siyang Sui; Hui Liu; Cheng Wu; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Chemistry, 2026)

Key aroma-active compounds and machine learning classification of chestnut baijiu revealed by molecular sensory, docking, and pathway analyses - Dan Li; Xinyue Zhang; Xiaohui Dou; Yujia Li; Yuchen Hou; Fumin Ma; Cuicui Duan; Xiaolei Li (Food Research International, 2026)

Exploration of the hypoglycemic effect and mechanism of Lactobacillus plantarum LH36 on type 2 diabetic mice through intestinal flora and non-targeted metabolomics - Cuicui Duan; Hui Liu; Siyang Sui; Hongru Wang; Yinfei Xing; Yixue Sun; Lifan Liu; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2026)

Structural identification and antioxidant activity of soybean protein isolate-exopolysaccharides-chlorogenic acid ternary complex - Cuicui Duan; Siyang Sui; Hongru Wang; Hui Liu; Yiming Yang; Yixue Sun; Lifan Liu; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2026)

Study on the characteristics of W1/O/W2 emulsion delivery system stabilized by soybean protein isolate/(−)-epigallocatechin gallate/exopolysaccharides complex - Cuicui Duan; Cheng Wu; Hui Liu; Siyang Sui; Hongru Wang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Research International, 2026)

Deciphering flavor profile and metabolic pathways in black chokeberry co-fermented by Lactiplantibacillus plantarum and Hansenula sp. via integrated volatilomics and metabolomics - Xiaolei Li; Wanxin Wang; Yujia Li; Fumin Ma; Cuicui Duan; Dan Li (Food Research International, 2026)

Enhanced suppression of retrogradation and digestibility in waxy rice starch by engineered mutants of GtfC type 4,6-α-glucanotransferase from Geobacillus sp. - Dan Li; Yuwei Liu; Cuicui Duan; Fumin Ma; Byung-Hoo Lee; Xiaolei Li (Food Bioscience, 2026)

Revealing the key aroma-active compounds and their potential metabolic pathways in Hongqu rice vinegar by integrating instrumental, sensory and statistical analysis - Xiaolei Li; Yujia Li; Fumin Ma; Cuicui Duan; Dan Li (International Journal of Gastronomy and Food Science, 2026)

Magnetic Fe-Mn spinel particle electrodes from red mud-shield slag wastes for 3D electrocatalytic dye degradation - Xinxin Li; Fumin Ren; Junshi Liu; Sibo Jia; Xiaoyu Ge; Houliang Guo (Journal of Environmental Management, 2026)

Plasma surface modification for inhibiting biofilm formation and immunomodulatory treatment of implant-related infections - Nongyang Yan; Fumin Yuan; Shuang Tan; Tengfei Li; Bichong Dai; Xiaoxue Bai; Wenchong Ouyang; Zhixin Ma; Hua Qiu; Zhengwei Wu; Zhenkun Xia (Chemical Engineering Journal, 2025)

Dispersal-related traits of mosses among fragmented habitats correlate highly with canopy closure rather than isolation - Jun Yang; Dandan Li; Xiao Wang; Yuzhu Xia; Tonghe Yuan; Fumin Lei; Jing Yu; Shuiliang Guo (Evolutionary Ecology, 2025)

Low-cost detection method for early-stage mildew in Hami melons based on hyperspectral image reconstruction using Sim-MST++ - Fujia Dong; Ying Xu; Benxue Ma; Fumin Dang; Yujie Li; Minghui Zhang; Fan Wu; Guowei Yu (Food Control, 2025)

Global synthesis of nitrogen management in sugarcane systems: Decoding climate-soil-management drivers of Brazil-China contrasts - Xiaomai Yuan; Shengsen Zhou; Fumin Wei; Li Ma; Yongfeng Sun; Dingjiao Peng; Run Liang; Yibao Luo; Baoshan Chen; Wei Yao; Ziting Wang (Field Crops Research, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Functional properties and sensitization of β-lactoglobulin were improved by covalent binding with exopolysaccharides and (−)-epigallocatechin gallate - Cuicui Duan; Yi Zhang; Cheng Wu; Siyang Sui; Hui Liu; Hongru Wang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

The effect and mechanism of Fe-modified coffee grounds hydrothermal carbon on the mass transfer efficiency of PMS and H2O2 advanced oxidation - Dahua Yu; Qingdan Liao; Xitong Li; Fumin Liu; Jingxin Huang; Huilin Guan; Yizong Huang (Journal of Water Process Engineering, 2025)

Island biogeography in urban landscapes: small island effect and nestedness in bryophyte communities of urban parks in Shanghai, China - Fumin Lei; Yiyi Shan; Dandan Li; Xiangzhang Wu; Jun Yang; Shuiliang Guo; Jing Yu (Urban Ecosystems, 2025)

Lateral resistance performance of embedded wall panels fabricated by fiber-reinforced foam concrete filled with crumb rubber powders - Ou Geng; Zhen Guo; Yulong Zhang; Fumin Li; Limin Lu (Innovative Infrastructure Solutions, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Exploration of the structural features and anti-oxidative activity of whey protein hydrolysates produced by Lactiplantibacillus plantarum - Cuicui Duan; Shunan Hu; Cheng Wu; Yi Zhang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Athyrium multidentatum (Doll.) Ching polysaccharide coated zein nanoparticles for oral delivery of resveratrol: Fabrication, characterization, stability and in vitro digestion - Fumin Ma; Wenxin Lv; Lei Wu; Cuicui Duan; Xiaolei Li; Dan Li (Food Bioscience, 2025)

An emulsion gel made by waxy maize starch hydrogel incorporated with tea polyphenols/exopolysaccharides: Structure and stability properties, antioxidant and delivery function - Cuicui Duan; Shunan Hu; Ran Wang; Cheng Wu; Yi Zhang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

Sub-chronic exposure of hexaconazole may induce metabolic and neuropathic diseases: The evidence from gut microbiota - Dali Sun; Tianming Yang; Min Wang; Junxiao Pang; Fumin Li (Pesticide Biochemistry and Physiology, 2025)

An exploration on the structural characteristics and antioxidant activities of casein hydrolysates fermented by Lactiplantibacillus plantarum A56 and A157 - Cuicui Duan; Lingfang Zhang; Cheng Wu; Yi Zhang; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

An exploration of the interaction, structural characterization and anti-oxidative properties of proanthocyanidin and beta-lactoglobulin complex - Cuicui Duan; Mengchun Qin; Lifan Liu; Yixue Sun; Lin Cai; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Efficient removal and recovery of phosphate by biochar loaded with ultrafine MgO nanoparticles - Yanpeng Huang; Qiong Wu; Jingfan Yan; Fumin Chu; Yuming Xu; Dongmin Li; Hongjia Zhang; Sen Yang (Environmental Research, 2025)

An Objective Synoptic Analysis Technique for the Identification of Tropical Cyclone Remote Precipitation in China and Its Application - Li Jia; Chenchen Ding; Chunhua Cong; Fumin Ren; Yanan Liu (Journal of Ocean University of China, 2025)

Insight into nitrogen removal through sulfate reducing anaerobic ammonia oxidation coupled with sulfur cycle: A comparative study on inorganic and organic conditions - Jiawei Li; Qianwen Sui; Fumin Zuo; Yiming Yang; Meixue Chen; Yuansong Wei (Journal of Environmental Management, 2025)

Simulation and experimental study on splitting performance of Rectifier Nozzle Type Critical Distributor for multi-parallel evaporators - Xiaofeng Li; Wenfu Zhang; Zhili Sun; Di Liang; Lei Yan; Haiwang Zhao; Jiale Chen; Fumin Hou; Xian Lv; Dandan Wang; Jiangman Yan (International Journal of Refrigeration, 2025)

Causal discovery and analysis of global city carbon emissions based on data-driven and hybrid intelligence - Xiaoyan Li; Wenting Zhan; Fumin Deng; Xuedong Liang; Peng Luo (Computers, Environment and Urban Systems, 2025)

Dynamic study of water distillation detritiation process startup using rigorous and ANN models - Zhiwei Zhang; Fumin Wang; Xiaohong Xiong; Zhengyu Zou; Shisheng Li; Changda Li; Jinhua Shi; Bingxin Zhu; Zheng Wang; Yang Qin; Yongwang Li; Qingzhao Liu; et al. (Journal of Water Process Engineering, 2024)

Different effects of resins and asphaltenes concentration of crude oil on sandstone wettability - Yaohui Xu; Gang Yan; Baofeng Hou; Kaiming Su; Fumin Zhang; Baolei Liu; Shanshan Li; Shouyu Zhao; Yan Liu (Fuel, 2024)

Characteristics and Preliminary Causes of Tropical Cyclone Remote Precipitation over China - Li Jia; Fumin Ren; John Leonard McBride; Chunhua Cong (Journal of Ocean University of China, 2024)

Unveiling causal dynamics and forecasting of urban carbon emissions in major emitting economies through multisource interaction - Xuedong Liang; Wenting Zhan; Xiaoyan Li; Fumin Deng (Sustainable Cities and Society, 2024)

Multispectral analysis and molecular docking to predict the mechanism of molecular interactions of curcumin, zein and fucoidan complexes - Yaqi Lu; Xiang Cai; Wenxin Lv; Cuicui Duan; Xiaolei Li; Fumin Ma; Dan Li (Journal of Food Engineering, 2024)

Introducing Ce into the interface of NiCo LDH@PBAs to build multi core–shell electrode with superior stability of supercapacitor - Jiawei Wang; Jiacheng Li; Fumin Wang; Xubin Zhang; Xu Wu; Juan Zhang; Shuai Niu; Liang Chen (Chemical Engineering Journal, 2024)

Alternations of antibiotic resistance genes and microbial community dynamics on shared bicycles before and after pandemic lockdown - Leshan Xiu; Haodong Liu; Yi Xie; Qinqin Hu; Huimin Li; Fumin Chen; Chenxi Wang; Yuqian Zhang; Liyuan Hou; Kun Yin (Science of The Total Environment, 2024)

Improving the matching degree between remotely sensed phenological dates and physiological growing stages of soybean by a dynamic offset-adjustment strategy - Siting Chen; Qiuxiang Yi; Fumin Wang; Jueyi Zheng; Jiale Li (Science of The Total Environment, 2024)

Modeling soybean cultivation suitability in China and its future trends in climate change scenarios - Qinyan Zhu; Fumin Wang; Qiuxiang Yi; Xiaoyang Zhang; Siting Chen; Jueyi Zheng; Jiale Li; Tianyue Xu; Dailiang Peng (Journal of Environmental Management, 2023)

Regulating lattice oxygen mobility of FeO redox catalyst via W-doping for enhanced chemical looping oxidative dehydrogenation of ethane - Xiaolin Zhu; Hongfei Guo; Ruiying Li; Hao Yan; Mingyuan Yang; Mengqi Wang; Fumin Yin; Xiao Yang; Chunyi Li; Chaohe Yang; Guowei Wang (Chemical Engineering Journal, 2023)

Fucoidan extracted by different methods and bound to zein loaded curcumin nanoparticles: Preparation, physicochemical stability, and in vitro functions - Yaqi Lu; Di An; Wenxin Lv; Xiang Cai; Fumin Ma; Dan Li (Food Bioscience, 2023)

Coordination number engineering of Zn single-atom sites for enhanced transfer hydrogenation performance - Yaping Song; Rou Guo; Binbin Feng; Yanghe Fu; Fumin Zhang; Yifei Zhang; De-Li Chen; Jiangwei Zhang; Weidong Zhu (Chemical Engineering Journal, 2023)

Revealing the dynamic temperature of the cathode catalyst layer inside proton exchange membrane fuel cell by experimental measurements and numerical analysis - Qianqian Wang; Fumin Tang; Xiang Li; Jim P. Zheng; Liang Hao; Guomin Cui; Pingwen Ming (Chemical Engineering Journal, 2023)

The mechanism of H2O in the superheated steam affecting the quality of in-situ pyrolysates of oil shale kerogen: Part B-favorable conversion of residues - Fumin Zhao; Bao Li; Daochang Che; Shengyu Liu (Fuel, 2023)

Physiological and Cytological Analyses of the Thousand-Grain Weight in ‘Zhongyan96-3’ Wheat - Luhua Li; Shuai Yang; Zhongni Wang; Mingjian Ren; Chang An; Fumin Xiong; Yuxuan Chen; Ruhong Xu (Journal of Plant Growth Regulation, 2023)

Simultaneous interfacial and bulk defect passivation and interface energy band alignment optimization via In(SCN2H4)3Cl3 diffusion doping for inverted perovskite solar cells - Dong Yang; Yujuan Weng; Zhitao Shen; Mengqi Jin; Hu Shen; Qing Du; Jihong Zheng; Fumin Li; Chong Chen (Chemical Engineering Journal, 2023)

Soil exposure is the major fluoride exposure pathways for residents from the high-fluoride karst region in Southwest China - Fumin Li; Shengmei Liao; Yifang Zhao; Xiangxiang Li; Zelan Wang; Chaoxuan Liao; Dali Sun; Qinghai Zhang; Qinhui Lu (Chemosphere, 2023)

Genome‐wide SNPs confirm plumage polymorphism and hybridisation within a Cyornis flycatcher species complex - Elize Y. X. Ng; Siqi Li; Dezhi Zhang; Kritika M. Garg; Gang Song; Jonathan Martinez; Le Manh Hung; Vuong Tan Tu; Jérôme Fuchs; Lu Dong; Urban Olsson; Yuan Huang; et al. (Zoologica Scripta, 2023)
Morphology has been a leading taxonomic guiding light to systematists for the last couple of hundred years. However, the genetic and – more recently – genomic revolution have produced numerous demonstrations of erroneous classifications that were based on labile morphological traits. We used thousands of genome‐wide markers to shed light on evolutionary dynamics in a confusing and taxonomically obscure group of Asian Cyornis flycatchers. Using genomic data, we corroborated recent findings based on three mitochrondrial and five nuclear genes that the two taxa hainanus and klossi which were previously treated as separate species ( Cyornis hainanus and Cyornis rubeculoides klossi , respectively) are genomically homogeneous and form a single species, C. hainanus . We also uncovered a novel case of interbreeding between C. hainanus and a non‐sister species, C. glaucicomans , illustrating these flycatchers' ability to hybridise in marginal situations even after substantial times of divergence. Our study illustrates how genome‐wide loci can shed light on complicated taxonomic problems, resulting in a better integration of phenotypic and genotypic data.

High-resolution numerical simulation of topographic influence on the heavy rainfall of Typhoon Rammasun - Xianling Jiang; Fumin Ren; Wenyu Qiu; Liguang Wu; Zhuguo Ma; Xun Li (Theoretical and Applied Climatology, 2022)

Exploring the environmental properties and resource utilization of construction waste in Beijing-Tianjin-Hebei region - Shuxin Hu; Fumin Ren; Jinming Jia; Can Cui; Changhong Guo; Nana Cui; Li Ma; Han Si; Tong Lu; Guotao Liu; Boyu Zhang; Junshi Liu (Environmental Science and Pollution Research, 2022)

Streptomyces akebiae sp. nov., a novel actinomycete isolated from rhizosphere soil of Akebia trifoliate - Ping Mo; Kaiqin Li; Jinhua Zhou; Fumin Zhou; Yazhi Chen; Xiaojia Lin; Xiaoyu Liu; Kerui Huang; Wansheng Zou; Jian Gao (Antonie van Leeuwenhoek, 2022)

Overexpression of TaLAX3-1B alters the stomatal aperture and improves the salt stress resistance of tobacco - Luhua Li; Dingli Hong; Chang An; Yuxuan Chen; Pengpeng Zhao; Xin Li; Fumin Xiong; Mingjian Ren; Ruhong Xu (Molecular Biology Reports, 2022)

Coordinated development of high-quality agricultural transformation and technological innovation: a case study of main grain-producing areas, China - Fumin Deng; Siyuan Jia; Meng Ye; Zhi Li (Environmental Science and Pollution Research, 2022)

Applying rail transit construction waste to make building materials: using the theory of sustainable development - Jinming Jia; Fumin Ren; Xiao Wei; Yinghao Gao; Gao Qi; Fuan Li; Ma Li; Changan Guo (Environmental Science and Pollution Research, 2022)

Biological Matrix Supply Chain Shortages: More Matrices Are Now Rare—the Case for Surrogate Matrices - Evan A. Dubiel; Heather Myler; Mark E. Arnold; Patrick Bennett; Jeff Gatz; Elizabeth Groeber; Seema Gupta; Cheikh Kane; Fumin Li; William Mylott; Courtney Noah; Mark O’Dell; et al. (The AAPS Journal, 2022)

Ecological and health risk assessment of heavy metals in soil and Chinese herbal medicines - Chunyan Meng; Peng Wang; Zhuolu Hao; Zhenjie Gao; Qiang Li; Hongxia Gao; Yingli Liu; Qingzhao Li; Qian Wang; Fumin Feng (Environmental Geochemistry and Health, 2022)

Changes in Typhoon Regional Heavy Precipitation Events over China from 1960 to 2018 - Yangmei Tian; John L. Mcbride; Fumin Ren; Guoping Li; Tian Feng (Advances in Atmospheric Sciences, 2022)
In earlier studies, objective techniques have been used to determine the contribution of tropical cyclones to precipitation (TCP) in a region, where the Tropical cyclone Precipitation Event (TPE) and the Regional Heavy Precipitation Events (RHPEs) are defined and investigated. In this study, TPE and RHPEs are combined to determine the Typhoon Regional Heavy Precipitation Events (TRHPEs), which is employed to evaluate the contribution of tropical cyclones to regional extreme precipitation events. Based on the Objective Identification Technique for Regional Extreme Events (OITREE) and the Objective Synoptic Analysis Technique (OSAT) to define TPE, temporal and spatial overlap indices are developed to identify the combined events as TRHPE. With daily precipitation data and TC best-track data over the western North Pacific from 1960 to 2018, 86 TRHPEs have been identified. TRHPEs contribute as much as 20% of the RHPEs, but 100% of events with extreme individual precipitation intensities. The major TRHPEs continued for approximately a week after tropical cyclone landfall, indicating a role of post landfall precipitation. The frequency and extreme intensity of TRHPEs display increasing trends, consistent with an observed positive trend in the mean intensity of TPEs as measured by the number of daily station precipitation observations exceeding 100 mm and 250 mm. More frequent landfalling Southeast and South China TCs induced more serious impacts in coastal areas in the Southeast and the South during 1990–2018 than 1960–89. The roles of cyclone translation speed and “shifts” in cyclone tracks are examined as possible explanations for the temporal trends.

Quantitative methods for predicting underground construction waste considering reuse and recycling - Rui Chen; Lanxin Li; Kai Yang; Fumin Ren; Chenggang Xi; Yang Lin; Hai Zheng (Environmental Science and Pollution Research, 2022)

Ecological risk assessment of heavy metals in farmland soils in Beijing by three improved risk assessment methods - Rui Chen; Xuying Cai; Guoyu Ding; Fumin Ren; Qi Wang; Nuo Cheng; Jiaxing Liu; Lanxin Li; Rongguang Shi (Environmental Science and Pollution Research, 2021)

Characteristics and Causes of Extreme Rainfall Induced by Binary Tropical Cyclones over China - Mingyang Wang; Fumin Ren; Yanjun Xie; Guoping Li; Ming-Jen Yang; Tian Feng (Asia-Pacific Journal of Atmospheric Sciences, 2021)
Binary tropical cyclones (BTC) often bring disastrous rainfall to China. From the viewpoint of the extreme of the BTC maximum daily rainfall, the characteristics of BTC extreme rainfall (BTCER) during 1960–2018 are analyzed, using daily rainfall data; and some representative large-scale mean flows, in which the associated BTCs are embedded, are analyzed. Results show that the frequency of BTCER shows a decreasing trend [−0.49 (10 yr) −1 ] and is mainly distributed within the BTC heavy rainstorm interval (100 mm ≤ BTCER

Establishment of an Objective Standard for the Definition of Binary Tropical Cyclones in the Western North Pacific - Fumin Ren; Yanjun Xie; Biwen Yin; Mingyang Wang; Guoping Li (Advances in Atmospheric Sciences, 2020)

Sideswiping Tropical Cyclones and Their Associated Precipitation over China - Tian Feng; Fumin Ren; Da-Lin Zhang; Guoping Li; Wenyu Qiu; Hui Yang (Advances in Atmospheric Sciences, 2020)

Severe Weather-Induced Exchange Flows through a Narrow Tidal Channel of Calcasieu Lake Estuary - Jie Wang; Chunyan Li; Fumin Xu; Wei Huang (Journal of Marine Science and Engineering, 2020)
Exchange flows between estuaries and the coastal ocean are important for land-ocean interactions and ecosystem health. This study is aimed at resolving severe weather-induced exchange flows between the Calcasieu Lake Estuary and Gulf of Mexico. For that purpose, we use data from a long-term deployment of side-looking acoustic Doppler current profilers (ADCPs) and conductivity-temperature-depth sensors (CTDs) as well as flow velocity data from a boat operated survey. Regression between the transport measured from a boat mounted ADCP and the velocity data from a fixed side-looking ADCP is done to calculate a long-term transport along the Calcasieu Pass. Analyses have been done for the hydrodynamic response to 16 cold fronts passing the study area. Effects of six strongest cold fronts are discussed in more detail. Results have confirmed that the hydrodynamics is highly correlated with the frequent cold fronts. The highest correlation coefficient is r ~0.75 between the north wind and along channel transport. In general, winds from the southern quadrants push water into the estuary before each frontal passage; after the passage of the front, a rapid change of wind direction to the northern quadrants produces strong outward flows. A quasi-steady state balance between the wind stress and water level difference proposed in recent studies for different systems is further confirmed and discussed in this system. The quasi-steady state balance leads to a relatively high R2 value of greater than 0.8 between the modeled water level gradient and actual observed gradient. We have also applied a regression model, derived from the momentum balance requirement, for the subtidal exchange flow as a function of wind components and their squares which yield an R2 value greater than 0.7. With a confidence in the regression model, we further implement it for twelve years from 26 February 2007 to 10 April 2019. Four extreme events during this 12-year period of time are discussed–they include the Hurricane Ike (2008), Tropical Storm Lee (2011), a warm front, and a cold front. This hindcast of the exchange flows over multiple years can provide a useful tool for coastal management and research for estuarine channels where continuous observations of velocity are not always available.

Assessing spectral indices to estimate the fraction of photosynthetically active radiation absorbed by the vegetation canopy - Dailiang Peng; Helin Zhang; Le Yu; Mingquan Wu; Fumin Wang; Wenjiang Huang; Liangyun Liu; Rui Sun; Cunjun Li; Dacheng Wang; Fubao Xu (International Journal of Remote Sensing, 2018)

Characteristics and Preliminary Causes of Tropical Cyclone Extreme Rainfall Events over Hainan Island - Xianling Jiang; Fumin Ren; Yunjie Li; Wenyu Qiu; Zhuguo Ma; Qinbo Cai (Advances in Atmospheric Sciences, 2018)

What makes the Sino‐Himalayan mountains the major diversity hotspots for pheasants? - Tianlong Cai; Jon Fjeldså; Yongjie Wu; Shimiao Shao; Youhua Chen; Qing Quan; Xinhai Li; Gang Song; Yanhua Qu; Gexia Qiao; Fumin Lei (Journal of Biogeography, 2018)
Aim The Sino‐Himalayas have higher species richness than adjacent regions, making them a global biodiversity hotspot. Various mechanisms, including ecological constraints, energetic constraints, diversification rate (DivRate) variation, time‐for‐speciation effect and multiple colonizations, have been posited to explain this pattern. We used pheasants (Aves: Phasianidae) as a model group to test these hypotheses and to understand the ecological and evolutionary processes that have generated the extraordinary diversity in these mountains. Location Sino‐Himalayas and adjacent regions. Taxon Pheasants. Methods Using distribution maps predicted by species distribution models ( SDM s) and a time‐calibrated phylogeny for pheasants, we examined the relationships between species richness and predictors including net primary productivity ( NPP ), niche diversity (NicheDiv), DivRate, evolutionary time (EvolTime) and colonization frequency using Pearson's correlations and structural equation modelling ( SEM ). We reconstructed ancestral ranges at nodes and examined basal/derived species patterns to reveal the mechanisms underlying species richness gradients in the Sino‐Himalayas. Results We found that ancestral pheasants originated in Africa in the early Oligocene (~33 Ma), and then colonized the Sino‐Himalayan mountains and other regions. In the Sino‐Himalayas, species richness was strongly related to DivRate, NPP , NicheDiv and colonization frequency, but weakly correlated with EvolTime. The direct effects of NicheDiv and DivRate on richness were stronger than NPP and EvolTime. NPP indirectly influenced species richness via DivRate, but its effect on richness via NicheDiv was relatively weak. Main conclusions Higher species diversity in the Sino‐Himalayas was generated by both ecological and evolutionary mechanisms. An increase in available niches, rapid diversifications and multiple colonizations was found to be key direct processes for the build‐up of the diversity hotspots of pheasants in the Sino‐Himalayan mountains. Productivity had an important but indirect effect on species richness, which worked through increased DivRate. Our study offers new insights on species accumulation in the Sino‐Himalayas and provides a useful model for understanding other biodiversity hotspots.

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Comparison of two drought indices in studying regional meteorological drought events in China - Yongmei Wang; Fumin Ren; Yilei Zhao; Yunjie Li (Journal of Meteorological Research, 2017)

Simulations of tropical cyclogenesis associated with different monsoon trough patterns over the western North Pacific - Xi Cao; Guanghua Chen; Tim Li; Fumin Ren (Meteorology and Atmospheric Physics, 2016)

Evolutionary history of Apocheima cinerarius (Lepidoptera: Geometridae), a female flightless moth in northern China - Shuxian Liu; Nan Jiang; Dayong Xue; Rui Cheng; Yanhua Qu; Xinxin Li; Fumin Lei; Hongxiang Han (Zoologica Scripta, 2016)
The alterations in the phylogeographical structures of insects in response to the uplift of the Qinghai–Tibet Plateau and the Quaternary glaciations in eastern Asia, particularly in northern China, remain largely unknown. In this study, we selected Apocheima cinerarius , a moth with flightless females, using molecular data (complete mitochondrial genomes and nuclear data) and ecological niche modelling ( ENM ) to investigate the effects of paleoclimatic changes on the evolutionary history of insects in the area of northern China. The phylogenetic tree of complete mitochondrial genomes indicated that there were two lineages, the western and eastern lineages. The nuclear gene analyses also detected unique haplotypes in each lineage. Time of the most recent common ancestor ( TMRCA ) of the two lineages was approximately in Early–Middle Pleistocene. Bayesian skyline plots revealed that the western lineage underwent a population expansion event after the Last Glacial Maximum, whereas the eastern lineage underwent expansion between the Last Interglacial and the Last Glacial Maximum. Our results suggest that A. cinerarius expanded eastward from western sites until the moth was distributed across the entire region of northern China. Then, A . cinerarius underwent contraction into isolated glacial refugia followed by subsequent expansion driven by Pleistocene climate changes, which established a narrow sympatric area. Our results indicate that the Quaternary environmental fluctuations had profound influences on the diversification and demography of an insect in northern China, and the same species in north‐western China and north‐eastern China have different demographic histories.

Complete mitochondrial genome sequence for the Malayan Pangolin Manis javanica (Pholidota, Manidae) - Weiye Li; Shiping Gong; Liushuai Hua; Yan Ge; Fumin Wang; Fanghui Hou (Conservation Genetics Resources, 2015)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

Genome analysis of Enterococcus faecalis bacteriophage IME-EF3 harboring a putative metallo-beta-lactamase gene - Xiaoyu Li; Peng Ding; Chuanyin Han; Hang Fan; Yahui Wang; Zhiqiang Mi; Fumin Feng; Yigang Tong (Virus Genes, 2014)

A regional extreme low temperature event and its main atmospheric contributing factors - Zhiqiang Gong; Guolin Feng; Fumin Ren; Jianping Li (Theoretical and Applied Climatology, 2014)

Characteristics of the regional meteorological drought events in Southwest China during 1960–2010 - Yunjie Li; Fumin Ren; Yiping Li; Pengling Wang; Hongming Yan (Journal of Meteorological Research, 2014)

Glacial expansion and diversification of an East Asian montane bird, the green‐backed tit ( Parus monticolus ) - Wenjuan Wang; Bailey D. McKay; Chuanyin Dai; Na Zhao; Ruiying Zhang; Yanhua Qu; Gang Song; Shou‐Hsien Li; Wei Liang; Xiaojun Yang; Eric Pasquet; Fumin Lei (Journal of Biogeography, 2013)
Aim We combined genetic sequence data and ecological niche modelling to resolve the impacts of past climatic fluctuations on the distribution, genetic diversification, and demographic dynamics of an East Asian montane bird, the green‐backed tit ( Parus monticolus ). Location East Asia. Methods Phylogenetic analyses were carried out using four mitochondrial fragments and seven nuclear loci from 161 birds sampled from 29 localities spanning the entire geographical range of the green‐backed tit. We used * beast to estimate the species tree and calculate divergence times. Extended Bayesian skyline plots were used to infer potential historical shifts in population size. We used MaxEnt to predict potential distributions during three periods: the present day, the Last Glacial Maximum and the Last Interglacial. Results The mitochondrial DNA (mt DNA ) gene tree showed strong support for three reciprocally monophyletic groups: a south‐western clade, a central clade and a Taiwanese clade. Taiwanese and Vietnamese samples had fixed differences at several nuclear loci, but the south‐western and central samples shared haplotypes at all nuclear loci. The mt DNA gene tree topology differed from the species tree topology. The species tree suggested sister relationships between Taiwanese and Vietnamese operational taxonomic units ( OTU s) and between south‐western and central OTU s. Diversification within the green‐backed tit was relatively recent, probably within the last 0.9 million years. Extended Bayesian skyline plots suggested rapid population expansion in the south‐western and central phylogroups after the Last Interglacial, and this result was consistent with ecological niche models. Main conclusions Our results suggest that genetic diversification within the green‐backed tit was affected by the later Pleistocene climate fluctuations. Ecological niche models indicated that the present‐day vegetation distribution was, in many ways, more similar to that of the Last Glacial Maximum than it was to that of the Last Interglacial. Continental populations of the green‐backed tit experienced unusual demographic and range expansion that is likely to have occurred during the cooling transition between the Last Interglacial and the Last Glacial Maximum. We found incongruence between the mt DNA gene tree and the species tree, which underscores the importance of using both mitochondrial and nuclear markers when estimating the evolutionary history of populations.

Incomplete lineage sorting or secondary admixture: disentangling historical divergence from recent gene flow in the V inous‐throated parrotbill ( P aradoxornis webbianus ) - Yanhua Qu; Ruiying Zhang; Qing Quan; Gang Song; Shou Hsien Li; Fumin Lei (Molecular Ecology, 2012)
Although P leistocene glaciations had a major impact on the population genetic patterns of many species in N orth A merica and E urope, it remains unclear how these climatic fluctuations contributed to species diversification in E ast A sia. One reason for this is the difficulty of distinguishing genetic admixture following secondary contact from incomplete lineage sorting, both of which can generate similar patterns of genetic variation. Using a combination of multilocus analyses and coalescent simulation, we explore how these two processes occurred in the P leistocene evolutionary history of a widespread E ast A sian bird, the V inous‐throated parrotbill, P aradoxornis webbianus . Maximum likelihood ( ML ) tree identified two major mitochondrial lineages, which are geographically separated in most parts of its range, but are sympatric at a few sampling sites. NJ tree and S tructure analysis of microsatellite data set revealed an extensive level of admixture and little population structure, suggesting recent admixture between two formerly separated groups. Networks from nuclear DNA data sets, however, did not indicate any geographically isolated groups but rather a panmictic population, thus support incomplete lineage sorting. By using coalescent simulation approaches, we show that both processes did occur, although at different temporal scales. During the P leistocene glaciations, probably around 0.1–0.5 Ma (the M arine I sotope S tage 6, MIS 6), P . webbianus contracted into two separate refugia, and subsequently accumulated genetic divergence. During the interglacial MIS 5, the species expanded into previously glaciated areas allowing the once separated groups to come into contact and become admixed. Taken together, our results indicate the current genetic variation within P . webbianus is a combination pattern of widespread distribution in pre‐ P leistocene, then contraction and fragmentation into separated refugia during glacial advance, followed by recently postglacial expansion and admixture.

A comparison of the adrenocortical responses to acute stress in cardueline finches from the Tibetan Plateau, Arctic Alaska and lowland Western North America - Dongming Li; Gang Wang; John C. Wingfield; Fumin Lei (Journal of Ornithology, 2012)

Simvastatin augments the efficacy of therapeutic angiogenesis induced by bone marrow-derived mesenchymal stem cells in a murine model of hindlimb ischemia - Yuqing Zhang; Rusheng Zhang; Yong Li; Guoping He; Dingguo Zhang; Fumin Zhang (Molecular Biology Reports, 2012)

Gender-Specific Association Between ACE Gene I/D Polymorphism and Blood Pressure Response to Hydrochlorothiazide in Han Chinese Hypertensive Patients - Yun Li; Peng Yang; Shouling Wu; Juxiang Yuan; Chong Shen; Ying Wu; Dandan Zhao; Qi Ren; Fumin Feng; Weijun Guan (Biochemical Genetics, 2011)

Organism–environment interactions in a changing world: a mechanistic approach - John C. Wingfield; J. Patrick Kelley; Fréderic Angelier; Olivier Chastel; Fumin Lei; Sharon E. Lynn; Brooks Miner; Jason E. Davis; Dongming Li; Gang Wang (Journal of Ornithology, 2011)

Variation in baseline corticosterone levels of Tree Sparrow (Passer montanus) populations along an urban gradient in Beijing, China - Shuping Zhang; Fumin Lei; Shenglin Liu; Dongming Li; Cong Chen; Peizhe Wang (Journal of Ornithology, 2011)

Impacts of the MJO on winter rainfall and circulation in China - Xiaolong Jia; Lijuan Chen; Fumin Ren; Chongyin Li (Advances in Atmospheric Sciences, 2011)

Movement patterns of Bar-headed Geese Anser indicus during breeding and post-breeding periods at Qinghai Lake, China - Peng Cui; Yuansheng Hou; Mingjie Tang; Haiting Zhang; Yuanchun Zhou; Zuohua Yin; Tianxian Li; Shan Guo; Zhi Xing; Yubang He; Diann J. Prosser; Scott H. Newman; et al. (Journal of Ornithology, 2011)

An extended time-dependent numerical model of the mild-slope equation with weakly nonlinear amplitude dispersion - Hongjun Zhao; Zhiyao Song; Fumin Xu; Ruijie Li (Acta Oceanologica Sinica, 2010)

Influences of tropical cyclones on China during 1965–2004 - Xiaoling Wang; Liguang Wu; Fumin Ren; Yongmei Wang; Weijing Li (Advances in Atmospheric Sciences, 2008)

Estimating tropical cyclone precipitation from station observations - Fumin Ren; Yongmei Wang; Xiaoling Wang; Weijing Li (Advances in Atmospheric Sciences, 2007)

Assessing the impact of Diplocardia ornata on physical and chemical properties of compacted forest soil in microcosms - F. Ponder Jr; Fumin Li; Diann Jordan; Edwin C. Berry (Biology and Fertility of Soils, 2000)